Current Status of Internship Training in Nepal - Shah, Santosh; Kumar, Anand; Chandra, Kailash (Journal of Universal College of Medical Sciences, 2019)
This is a perspective article about the status of undergraduate medical internship training in Nepal based on the learned experience and reflections on current practices on medical education in Nepal. The medical education in Nepal is facing myriad challenges. In order to keep up with the current demands and advances in medical education, adaptation and changes in current curriculum and its modalities are crucial. Current medical curriculum, specifically needs to focus on promoting communication skills, community based learning and medical ethics which may help to garner skills and motivate students for innovations and research in the field.